Instantaneous and historical temperature effects on α -pinene emissions in Pinus halepensis and Quercus ilex - Blanch, Josep-salvador; Llusia, Joan; Niinemets, Ülo; Noe, Steffen M.; Penuelas, Josep (Journal of Environmental Biology, 2011)
We compared the role of instantaneous temperature and temperature history in the determination of α-pinene emissions in Mediterranean conifer Pinus halepensis that stores monoterpenes in resin ducts, and in Mediterranean broad-leaved evergreen Quercus ilex that lacks such specialized storage structures. In both species, α-pinene emission rates (E) exhibited a significant exponential correlation with leaf temperature and the rates of photosynthetic electron transport (JCO 2 +O 2 ) started to decrease after an optimum at approximately 35 o C. However, there was a higher dependence of E on mean temperature of previous days than on mean temperature of current day for P. halepensis but not for Q. ilex. JCO 2 +O 2 showed a maximum relationship to mean temperature of previous 3 and 5 days for P. halepensis and Q. ilex respectively. We conclude that although the best correlation of emission rates were found for instantaneous foliar temperatures, the effect of accumulated previous temperature conditions should also be considered in models of monoterpene emission, especially for terpene storing species.
Keywords: acclimation; emission model; Pinus halepensis; previous climate effects; Quercus ilex

Light and temperature dependence of the emission of cyclic and acyclic monoterpenes from holm oak (Quercus ilex L.) leaves - Staudt, M; Bertin, N (Plant, Cell & Environment, 1998)
In a laboratory study, we investigated the monoterpene emissions from Quercus ilex, an evergreen sclerophyllous Mediterranean oak species whose emissions are light dependent. We examined the light and temperature responses of individual monoterpenes emitted from leaves under various conditions, the effect of heat stress on emissions, and the emission-onset during leaf development. Emission rate increased 10-fold during leaf growth, with slight changes in the composition. At 30 °C and saturating light, the monoterpene emission rate from mature leaves averaged 4·1 nmol m–2 s–1, of which α-pinene, sabinene and β-pinene accounted for 85%. The light dependence of emission was similar for all monoterpenes: it resembled the light saturation curve of CO2 assimilation, although monoterpene emission continued in the dark. Temperature dependence differed among emitted compounds: most of them exhibited an exponential increase up to 35 °C, a maximum at 42 °C, and a slight decline at higher temperatures. However, the two acyclic isomers cis-β-ocimene and trans-β-ocimene were hardly detected below 35 °C, but their emission rates increased above this temperature as the emission rates of other compounds fell, so that total emission of monoterpenes exponentially increased from 5 to 45 °C. The ratio between ocimene isomers and other compounds increased with both absolute temperature and time of heat exposure. The light dependence of emission was insensitive to the temperature at which it was measured, and vice versa the temperature dependence was insensitive to the light regime. The results demonstrated that none of the models currently applied to simulate isoprene or monoterpene emissions correctly predicts the short-term effects of light and temperature on Q. ilex emissions. The percentage of fixed carbon lost immediately as monoterpenes ranged between 0·1 and 6·0% depending on temperature, but rose up to 20% when leaves were continuously exposed to temperatures between 40 and 45 °C.
Keywords: biogenic VOC emission; emission model; heat stress; Holm oak; Isoprenoids; light effect; Monoterpenes; Quercus ilex; temperature effect